Antioxidant ability of 1-phenyl-3-(2-pyridyl)-2-thiourea: combined experimental/computational studies - Đinh , Quý Hương; Trần, Đồng Linh Chi (Hue University Journal of Science: Natural Science, 2021)
2,2-Diphenyl-1-picrylhydrazyl (DPPH•) and 2,2'-azinobis (3-ethylbenzothiazoline-6-sulfonate) (ABTS•+) were used in this study. IC50 values of 1-phenyl-3-(2-pyridyl)-2-thiourea (PPTU) with DPPH• and ABTS•+ are 1.3 × 10-3 and 1.1 × 10-3 M. Quantum chemical calculations were performed at the M05-2X/6-311++G(d,p) level to construct a potential surface of the reaction and calculate the rate constants according to hydrogen atom transfer (HAT) and single electron transfer (SET) mechanisms. The reaction between PPTU and HOO• free radicals mainly occurs with the HAT mechanism. The portion of product under this mechanism accounts for 99.99% of the total products. N2-H17 is the most favored hydrogen transfer position in the PPTU molecule with the rate constant of 1.44 × 10-1 M-1·s-1.